Workplace ostracism, Syrian migrant workers' counterproductive work behaviors, and acculturation: Evidence from Turkey. (March 2021) - Gürlek, Mert
Abstract: This research aims to investigate the effect of workplace ostracism on counterproductive work behavior (CWB) and the moderating role of acculturation in this respect. The relationships between variables are analyzed through structural equation modeling. The data are collected from Syrian migrant workers in the restaurant industry in Istanbul, Turkey (n = 392), and the results indicate that workplace ostracism has a positive effect on CWB. Besides, acculturation plays a moderator role in the effect of workplace ostracism on CWB. In this regard, acculturation differentiates the relationship between the two variables. The present study contributes to the related theory by revealing that workplace ostracism drives less CWB among Syrians adopting the host culture and more of it among those maintaining the origin culture.